Training on Clean Water Treatment Using Slow Sand Filters And Biomass Filters at Bahrul Magfiroh Islamic Boarding School Malang City - Herlina, Sri; Ramadhan, Majida; Widiyana, Anita Puspa; Rahmatullah, Muhammad Ali; Rofiq, Muhammad Fadlan (LPPM Universitas Yudharta Pasuruan, 2023)
The purpose of this activity is to increase students' knowledge about PHBS and diarrhea prevention using herbal ingredients as well as the application of clean water treatment simulations using slow sand filter and biomass filter methods. This method of implementing service uses a participatory and collaborative approach through active and interactive discussions. This activity was carried out by involving 54 students of Bahrul Magfiroh Islamic Boarding School Malang. Service participants directly practice and understand the function of applying water treatment devices and the use of herbal ingredients for the prevention of diarrhea. The results of activities on clean water treatment are almost 90% understood by students, both the use of biomass filters and slow sand filters, while 42.6% of students still have a low understanding of how to process herbal ingredients for the prevention of diarrhea. The importance of continuous training on increasing knowledge of clean and healthy living behavior must continue to be improved as an effort to prevent the risk of disease transmission and health problems, including maintaining personal health and the Islamic boarding school environment.